(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the tourism and recreational potential of the shrines and pilgrimage sites of the Fergana Valley. It reveals the relationship between pilgrimage and recreational tourism, their social, cultural and economic significance. It presents analytical data on the main shrines and pilgrimage sites of the Fergana Valley, the leading factors in their formation, existing natural and historical monuments. Recommendations have been developed to increase the spiritual, economic and recreational potential of the region through the development of tourism focused on shrines.